LEGAL HARMONIZATION BETWEEN THE OMNIBUS LAW AND BASIC AGRARIAN LAW (UUPA) IN PROTECTING INDIGENOUS RIGHTS - Ulfia Hasanah; Nia Kurniati; Maret Priyanta (Cepalo, 2025)
Harmonizing the Basic Agrarian Law (UUPA) and the Omnibus Law is crucial for protecting indigenous rights in Indonesia. The UUPA emphasizes people’s sovereignty over land and recognizes customary land rights, whereas the Omnibus Law focuses on liberalizing land management to accelerate investment and national projects. As a rule of law country, Indonesia must balance economic growth with human rights protection, including those of indigenous communities. Law No. 6 of 2023 on Job Creation has intensified challenges, as the Omnibus Law’s streamlined land permits grant the government broad powers often overlooking customary rights. To address this, the Free, Prior, and Informed Consent (FPIC) mechanism should be implemented to align development with indigenous rights. Additionally, revising the Omnibus Law’s derivative regulations to explicitly recognize customary land rights and establishing a dedicated agency to resolve related disputes are necessary. A holistic policy reform reflecting the UUPA’s principles while accommodating the Omnibus Law will ensure development that is both just and sustainable. Improved harmonization will allow Indonesia to pursue economic progress without sacrificing social justice and indigenous rights.